PENGARUH INTERAKSI SOSIAL GURU DENGAN SISWA TERHADAP MOTIVASI BELAJAR DI JURUSAN TEKNIK GAMBAR BANGUNAN SMK NEGERI 1 CILAKU CIANJUR - Iswardhany, Rieske (2013)
Social interaction between student and teacher is a key factor to build student motivation. Enthusiasm member, good environment, familiarity is also needed in studying or learning process. Those points will be achieved maximal output result.This research pointing in 1) mechanism studying or learning process between members in majors TGB SMK Negeri 1 CilakuCianjur; 2) motivation illustration in majors TGB SMK Negeri 1 CilakuCianjur; 3) Influence of social interaction between teacher and student relationship and also student motivation in majors TGB SMK Negeri 1 CilakuCianjur. This research isdescriptiveusinga quantitative approach. Data collection instrument using questionnaires, Sample of research total 66 student population class of XI TGB SMK Negri 1 Cilaku Cianjur. From the analysis of the data obtained a relationship between two variables is positive and significant, overview of social interaction of students and teachers in both criteria. General from student motivation in majors TGB SMK Negeri 1 Cilaku Cianjur is high. Based on the criteria for the interpretation of the correlation coefficient, the relationship between the two variables included in the strong category. Keywords: Social interaction, Motivation, Learning